Lukiana z Samosat traktat „Jak należy pisać historię” i jego znajomość w pismach dotyczących refleksji historiograficznej w dawnej Polsce - Lewandowski, Ignacy (Studia Europaea Gnesnensia, 2012)
The article contains a short presentation of the treatise entitled How to write history. The hand which wrote it was Lucian of Samosata’s, a Greek rhetor and sophist (2nd cent.). It is the sole treatise concerning methodology of history that the antiquity left us. Knowledge of the text is also transparent in the writings of authors who created on the territory of the Polish “Republic of the Gentry” in the 16th and 17th cent., and who were keen on historiographic reflection, such as Stanisław Iłowski, Jan Firlej of Dąbrowica, Bartłomiej Keckermann and Szymon Starowolski.